Impact of stigma and stigma-focused interventions on screening and treatment outcomes in cancer patients - Akin-Odanye, Elizabeth O; Husman, Anisah J (Ecancermedicalscience, 2021)
Stigma is known to negatively influence cancer patients' psychosocial behaviour and treatment outcomes. The aim of this study was to systematically review the current data on cancer-related stigma across different populations and identify effective interventions used to address it. The protocol, search, appraisal, synthesis, analysis and reporting framework was used for conducting this systematic literature review. CINAHL, PubMed, PsycINFO and Google Scholar databases were searched using the different combination of keywords that include 'cancer stigma'. Articles publication period was set for 2010-2020. A total of 54 articles (31 quantitative, 19 qualitative, 2 mixed methods and 2 scoping reviews) that met inclusion criteria were reviewed out of the 958 articles initially identified. Quality assessment of included studies revealed the studies had varying levels of methodological quality. Extracted data were organised and narratively analysed. Cancer stigma was expressed across different segments of the society including amongst the elites and healthcare providers. Developing countries had higher rates of stigma reported and experience of stigma varied by cancer type. Cancer was consistently associated with imminent death in all studies reviewed. Cancer patients experiencing stigma were more inclined to conceal their diagnosis and to seek medical help later. Whilst cancer stigma majorly resulted in negative psychosocial outcomes in patients, there were also instances of posttraumatic growth emanating from the stigma experienced. Literature on cancer-related stigma interventions was scant. Cancer related stigma remains high in both clinical settings and amongst the general public. There is need for more interventions to combat cancer stigma and its effect in both patient and non-patient population. Anti-cancer public enlightenment campaigns should be sensitively designed to not further fuel stigma against patients with certain types of cancers.